Pengaruh Penggunaan Smartphone Terhadap Aktivitas Ibadat Orang Muda Katolik (OMK) di Paroki Maria Ratu Pencinta Damai Lolah - Tasya Lucia Kandow; Adrianus Dalia; Marianus Muharli Mua (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2024)
Usage smartphone have positive and negative influences. Use which are not in accordance with their function can have an impact on OMK worship activities at Maria Ratu Lolah Peace Lolah Parish. This research is to find out how to usesmartphone OMK, OMK worship activities, and how big the influence of usesmartphone on OMK worship activities at Maria Ratu Lolah Peace Lolah Parish. The method used for this research is quantitative research. The respondents were all OMK in Lolah Mary Queen Peace Parish which was determined by the Slovin formula so that the total number of respondents was 175 OMK with a total of 310 OMK. The research instrument used is by distributing questionnaires or questionnaires with alternative answers to variable X (usesmartphone) namely Strongly Agree (4), Agree (3), Disagree (2), and Disagree (1) and alternative answers to variable Y (worship activities) namely Always (4), Often (3), Rarely (2) , and Never (1). Simple linear regression analysis. The research results obtained show that the usesmartphone OMK obtained a calculated coefficient of 0.86 and was in the very good category, OMK worship activities obtained a calculated coefficient of 0.90 and were in a very good category as well as the influence of usingsmartphone towards worship activities with a determination coefficient of 0.467. From these results, by looking at the coefficient interval, it is categorized as moderate with a percentage of 46% and 54% influenced by other factors.